Politics and reflection - Bruce, SJ (2020)
In public discussion and political philosophy alike, there are frequent calls for citizens and politicians to be more “reflective”. However, it is not always clear what this means. This thesis investigates what the political practice of reflection entails and why we should engage in it. After setting out the wide range of contemporary political problems reflection is thought to solve, I outline the broad definitional contours of the concept as I understand it, distinguishing it from other such related terms as ‘deliberation’ in the first chapter.